Influence of different photoinitiators on the resistance of union in bovine enamel: an in vitro study (Research, Society and Development, 2020)
To evaluate the action of photoinitiators on the microtensile resistance of adhesive systems and resins composed in bovine enamel. Forty dental fragments, with flat and smooth enamel surfaces, obtained from the coronary buccal face of healthy bovine incisors, were randomly assigned to 4 experimental groups (n = 10) according to the different adhesive systems and composite resins used: Group 1- Ambar APS + Vittra APS; Group 2- Ambar APS + Opallis; Group 3- Ambar + Vittra APS; Group 4- Ambar + Opallis. After composite restoration, the samples were sectioned to obtain toothpicks that were subjected to the microtensile test (1.0 mm/min). The data obtained were subjected to statistical analysis. The Kruskal-Wallis test revealed no significant differences between groups (p